Influence of Extra-Articular Augmentation on Clinical Outcomes and Survival in Patients Undergoing Anterior Cruciate Ligament Reconstruction: A Pseudorandomized Study - Antonio Maestro; Nicolás Rodríguez; Iván Pipa; Carmen Toyos; Lucía Lanuza; Filipe Machado; César Castaño; Santiago Maestro (Medicina)
Background and Objectives: Up to 27% of anterior cruciate ligament (ACL) reconstruction cases result in a residual positive pivot shift sign, indicating anteroposterior and rotational instability. This instability can compromise returning to sports and increase the risk of further injuries. The biomechanical role of the anterolateral ligament (ALL) in controlling internal knee rotation is well known. However, there are no clinical trials comparing isolated ACL repairs to those combined with ALL reconstruction. Our objective is to compare the results of these techniques, with a primary focus on assessing knee stability and graft survival, to provide evidence for optimizing surgical approaches, particularly for athletes and physically active individuals. Materials and Methods: An observational study using paired score matching as a method of pseudo-randomization was conducted. Subjects were divided into an ACL group and an ACL+ALL group. Demographic and clinical variables were collected, as well as those related to complications and survival. Results: A total of 236 patients were included, which was reduced to 74 ACL and 37 ACL+ALL after pseudo-randomization, resulting in preoperatively comparable groups. During follow-up, differences in favor of ALL reinforcement were found on the pivot shift test (p = 0.007). No differences were found with regard to the Lachman test (p = 0.201), the International Knee Documentation Committee (IKDC) knee score (p = 0.169), the IKDC subjective score (p = 0.095), intensity of pain (p = 0.928), or complications (p = 0.529). Nor were differences found in the limb symmetry index; the single hop test (p = 0.710); the triple hop test (p = 0.653); the crossover hop test (p = 0.682); the 6 meter timed hop test (p = 0.360); the normalized Y-balance test (YBT) (p = 0.459 anterior; p = 0.898 posterolateral; and p = 0.211 posteromedial directions); or the limb symmetry index of the composite YBT (p = 0.488). There were no differences either with respect to return to sports practice (p = 0.723) or survival (p = 0.798). Conclusions: Patients treated by means of the ACL+ALL technique obtained higher rotational stability, as measured by the pivot shift test, than those subjected to an isolated ACL repair. No differences were found with respect to Lachman test, complications, IKDC, pain, or survival.